Environmental excellence district program assessment according to the strategy self-management promotion of the sustainable production for capital district policy (2017)
(Eng) This article presents the methodology and results obtained from the Environmental Excellence District Program - PREAD - assessment, which belong’s to the Secretaría Distrital de Ambiente - SDA- program who is in charge to feed the District information systems, according to the active industry in Bogotá city, quantifying their environmental impacts, classifying their performances and efficiencies, determining market trends and encouraging the postulated and improvement of environmental management systems giving public acknowledgements to companies with the best environmental performances. This assessment used as a methodological basis the Strategic Environmental Assessment - EAE - tool used for the analysis of public policies which use an environmental development looking that is not in the scope of Environmental Impact Studies - EIA-, because them only analyze quantitatively aspects and environmental impacts but leave out political and administrative aspects related to the prospective analysis of public policies. Took into account the program evolution over time, considering the periods 2001-2003 and 2004-2013, deficiencies in documentation and continuous monitoring improvement and built the perception of the enterprises in the city about the program and the institutions responsible for its implementation, through a random sampling, in order to formulate tools for its improvement and updating. Finally, recommendations for postulated in all stages of the program are structured, taking into account the inter-institutional communication, the documentary record, quality control and communication protocols and interaction with the population object for the program and inclusive policies in this.